A scoping review and mapping exercise comparing the content of patient-reported outcome measures (PROMs) across heart disease-specific scales - Beatrix Algurén; Michaela Coenen; Dan Malm; Bengt Fridlund; Jan Mårtensson; Kristofer Årestedt; on behalf of the Collaboration and Exchange in Swedish cardiovascular caring Academic Research (CESAR) (SpringerOpen, 2020)
Abstract Background Over the past decade, the importance of person-centered care has led to increased interest in patient-reported outcome measures (PROMs). In cardiovascular care, selecting an appropriate PROM for clinical use or research is challenging because multimorbidity is often common in patients. The aim was therefore to provide an overview of heart-disease specific PROMs and to compare the content of those outcomes using a bio-psycho-social framework of health. Methods A scoping review of heart disease-specific PROMs, including arrhythmia/atrial fibrillation, congenital heart disease, heart failure, ischemic heart disease, and valve diseases was conducted in PubMed (January 2018). All items contained in the disease-specific PROMs were mapped to WHO's International Classification of Functioning, Disability and Health (ICF) according to standardized linking rules. Results A total of 34 PROMs (heart diseases in general n = 5; cardiac arrhythmia n = 6; heart failure n = 14; ischemic heart disease n = 9) and 147 ICF categories were identified. ICF categories covered Body functions (n = 61), Activities & Participation (n = 69), and Environmental factors (n = 17). Most items were about experienced problems of Body functions and less often about patients' daily activities, and most PROMs were specifically developed for heart failure and no PROM were identified for valve disease or congenital heart disease. Conclusions Our results motivate and provide information to develop comprehensive PROMs that consider activity and participation by patients with various types of heart disease.